Acute response in circulating microRNAs following a single bout of short-sprint and heavy strength training in well-trained cyclists - Ryningen, A.; Rostad, K.; Ersvær, E.; Bjørkhaug, L. (Frontiers in Physiology, 2024)
Background: Heavy strength (HS) and short-sprint (SS) are commonly used training methods for competitive road cyclists, with the aim to improve the anaerobic power and short time cycling performance. Knowledge of how such training methods affects biochemical as well as molecular factors, are particularly important for determining individual recovery and long-term adaptations. The primary aim of the current study was to investigate the expression levels of small non-coding RNAs in response to HS and SS training in elite cyclists as potential biomarkers for individual optimal restitution time.